SlowFaster, a user-friendly program for slow-fast analysis and its application on phylogeny of Blastocystis - Kostka, Martin; Uzlikova, Magdalena; Cepicka, Ivan; Flegr, Jaroslav (BMC bioinformatics, 2008)
BACKGROUND: Slow-fast analysis is a simple and effective method to reduce the influence of substitution saturation, one of the causes of phylogenetic noise and long branch attraction (LBA) artifacts. In several steps of increasing stringency, the slow-fast analysis omits the fastest substituting alignment positions from the analysed dataset and thus increases its signal/noise ratio. RESULTS: Our program SlowFaster automates the process of assessing the substitution rate of the alignment positions and the process of producing new alignments by deleting the saturated positions. Its use is very simple. It goes through the whole process in several steps: data input - necessary choices - production of new alignments. CONCLUSION: SlowFaster is a user-friendly tool providing new alignments prepared with slow-fast analysis. These data can be used for further phylogenetic analyses with lower risk of long branch attraction artifacts.
Keywords: Computational Biology; Phylogeny; protozoální DNA; User-Computer Interface; sekvenční seřazení; Sequence Alignment; časové faktory; Animals; Time Factors; Blastocystis; zvířata; uživatelské rozhraní počítače; DNA, Protozoan; výpočetní biologie; fylogeneze